Planar cell polarity signalling coordinates heart tube remodelling through tissue-scale polarisation of actomyosin activity - Anne Margarete Merks (Nature Portfolio, 2018)
The molecular mechanisms underlying cardiac chamber formation are not well understood. Here, the authors show that planar cell polarity signalling through Wnt5b and Wnt11 coordinates localised and tissue-scale polarised actomyosin contractility in the zebrafish heart, regulating cardiac chamber formation and looping.